English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

use elimination to solve the system of equation:

3x + 7y = -43
7x + 6y = -59

2006-11-01 12:18:33 · 6 answers · asked by SICK MY DUCK! 1 in Science & Mathematics Mathematics

6 answers

Okay multiply the top equation by 7 and the bottom equation by negative 3 to obtain 2 new equations with the x variable to eliminate:

7(3x + 7y = -43)
-3(7x + 6y = -59)

this becomes

21x + 49y = -301
-21x - 18y = 177

Now cancel out the 21x's and add down. Doing that, the equation becomes

31y = -124 this can easily be solved for y

y = -4

Now plug -4 back into one of the original equations

3x + 7(-4) = -43

3x - 28 = -43

add 28 to both sides to yield

3x = -15 and solve for x

x = -5

Now check x = -5 and y = -4 into both and see that you have solved this system correctly.

2006-11-01 12:29:42 · answer #1 · answered by Anonymous · 0 0

First, find the equivalent of x or y in terms of the other one.
3x + 7y = -43
x = (-43 - 7y)/3
Then, you use that value for the second equation
7*((-43 - 7y)/3) + 6y = -59
7*-43/3 - 7*7y/3 + 6y = -59
6y - 49/3y = -59 + 301/3
-31y/3 = 124/3
y = -124/31
y = -4
Then, with this value, you resolve one of the 2 equations:
3x + 7y = -43
3x +7*-4 = -43
x = (-43 + 28)/3
x = -5

2006-11-01 20:26:49 · answer #2 · answered by Chemielieber 3 · 0 0

You use elimination....

Basically you gotta make either X or Y both equal in those equations then you subtract one from the other so you end up with one variable. Solve the variable then plug it into one of the equations again to find the variable you just canceled out.

An exampe would be taking 3x+7y=-43 and multiplying each term by 7/3 to make the X term equal to the 7X in the other equation. Then you would actually subtract one equation form the other which would obviously cancel out the X term. The resulting equation lets you solve for Y. Once you have your ansewr for Y, plug it into one of the equations to find X and you're done.

2006-11-01 20:22:52 · answer #3 · answered by Roman Soldier 5 · 0 0

3x+7y=-43
7x+6y =-59
Multiply the first equation by 7 and the second by -3 to get:
21x+49y= -301
-21x -18y = 177
31y = - 124
y = - 4
Now stick y = -4 into the first equation to get:
3x+7(-4)=-43
3x-28 =-43
3x= -15
x=-5

2006-11-01 20:29:36 · answer #4 · answered by ironduke8159 7 · 0 0

3x + 7y=-43
7x + 6y=-59

first u need to get rid of either the x's or y's so you can times the to by -7, and the bottem by 3 so you get...
-21x - 49y= 301 than u add them like so
+ 21x + 18y= -177
------------------------
0x - 31y= 124

y= - 4
than you plug in y to one of the equations and solve for x

2006-11-01 20:28:07 · answer #5 · answered by scherdaddy 1 · 0 0

dc

2006-11-01 20:22:47 · answer #6 · answered by Anonymous · 0 0

fedest.com, questions and answers